Smartphone bans and workplace performance - Adrian Chadi; Mario Mechtel; Vanessa Mertins (Experimental Economics, 2021)
This paper constitutes the first economic investigation into the potential detrimental role of smartphones in the workplace based on a field experiment. We exploit the conduct of a nationwide telephone survey, for which interviewers were recruited to work individually and in single offices for half a day. This setting allows to randomly impose bans on the use of interviewers' personal smartphones during worktime while ruling out information spillovers between treatment conditions. Although the ban was not enforceable, we observe substantial effort increases from banning smartphones in the routine task of calling households, without negative implications linked to perceived employer distrust. Analyzing the number of conducted interviews per interviewer suggests that higher efforts do not necessarily translate into economic benefits for the employer. In our broad discussion of smartphone bans and their potential impact on workplace performance, we consider further outcomes of economic relevance based on data from employee surveys and administrative phone records. Finally, we complement the findings of our field experiment with evidence from a survey experiment and a survey among managers.
Keywords: M50; J24; C93; 330; Smartphone ban; Control; Trust; Workplace behavior; Effort choice; Field experiment